Determining performance indicators and developing tools for evaluating BRAC Gonokendra Pathagar (Library) - Khan, Md. Kaisar Ali (BRAC Research and Evaluation Division (RED), 2020)
This study aimed at determining major performance indicators as well as developing tools for evaluating BRAC's Gonokendra Pathagars (community-based libraries). Twelve performance indicators have been determined. A format has also been developed as a data collection tool where all the selected indicators have been accommodated. The format includes two additional formats that can be used to fill up some columns of the main data collection format. Besides, a supplementary tool (a set of score tables) has been developed which can be used in putting scores against the data that will be collected from the pathgars. This paper demonstrates an implementation procedure of the tools using some real data, which were gathered from different type of pathagars. These evaluation tools may be used by the programme itself for regular monitoring and evaluating BRAC pathagars.